Hierarchy of the B (MHC) haplotypes controlling resistance to rous sarcomas in a model of inbred lines of chickens - Plachý, J (Folia biologica, 1984)
The effects of individual B haplotypes on regression of Rous sarcoma virus-induced tumours were studied in a genetically defined model of congenic chicken lines differing at the B complex (MHC). Regression of Rous sarcomas is genetically controlled mainly by B genes the effects of which are qualitative in nature. In the model described which encompassed congenic inbred lines and their F1 hybrids and a number of various combinations of progeny from backcross matings, the genetic interactions among individual B haplotypes and the modifying influence of the genetic background, as manifested by quantitative variability of tumour growth parameters, could also be investigated. Some specific combinations of backcross progeny exhibited significant shifts with regard to basic classification of the degree of resistance of groups with a given B genotype in the congenic lines and their F1 hybrids. Based on these differences, further more detailed studies of the complex genetic mechanism operative in the control of tumour growth may be undertaken. Discriminant analysis, as part of the known series of the biomedical programs BMDP75, was used to evaluate the results.
Keywords: ptačí sarkom; Sarcoma, Avian; hlavní histokompatibilní komplex; Immunity, Innate; kur domácí; viry ptačího sarkomu; Animals; Histocompatibility Antigens Class II; MHC antigeny II. třídy; Avian Sarcoma Viruses; Major Histocompatibility Complex; Chickens; zvířata; přirozená imunita